AI-gamified teaching in music education: Implications for student learning and engagement - Meiyu Li; Thanin Ratanaolarn; Sirirat Petsangsri (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores how blending AI and gamification boosts music theory learning and student engagement, a gap in current research. A 14-week quasi-experiment with 180 first-year music students (90 per group) compared an AI-gamified approach to traditional teaching. Pre-tests found no differences in initial proficiency (EG: 52.18±8.36; CG: 51.75±8.62) or engagement. Post-intervention, the AI-gamified group scored 83.42±7.45 in music theory—far higher than the control’s 62.31±9.18 (p<0.001)—with 59.9% improvement versus 20.4%. They also excelled in behavioral, emotional, cognitive, and social engagement (all p<0.001), with overall scores of 52.38±5.76 versus 39.72±6.93. Success stems from gamification fueling intrinsic motivation, AI tailoring guidance, and tech easing collaboration. The findings back using such tools in music classes, with educator training in adaptive methods advised. Limitations include a small, short-term sample; future work should explore long-term impacts and individual variations.
Keywords: Diverse Music Education Insights; Educational Games and Gamification; Neuroscience and Music Perception